Analysis and Optimization of Differential Abnormal Noise Tests for Low Speed Steering - Jun Zhang; Yongzhong Bao; Shengxiang Chu; Hanfang Zhang (Jixie chuandong)
Differential is one of the important parts of automobile transmission system. The analysis of its fault mode and the control of it have always been the focus in the automotive industry. Thus， an analysis and investigation process of the abnormal noise problem is systematically expounded based on a CVT sedan low-speed steering condition. The reproduction of the abnormal noise problem is realized through the differential performance bench. Combined with the disassembly analysis of the fault parts， the potential mechanism and solution of differential abnormal sound problem are proposed. Through the optimization of planetary shaft positioning assembly method and processing technology， the abnormal sound of the differential of the vehicle is accurately and effectively eliminated, which has certain engineering guidance value for the solution and investigation of NVH（Noise， Vibration， Harshness） and abnormal sound problems of the transmission system under transient working conditions of the vehicle.